Abstraction by symbolic indexing transformations - Melham, T; Jones, R (Springer, 2002)
Symbolic indexing is a data abstraction technique that exploits the partially-ordered state space of symbolic trajectory evaluation (STE). Use of this technique has been somewhat limited in practice because of its complexity. We present logical machinery and efficient algorithms that provide a much simpler interface to symbolic indexing for the STE user. Our logical machinery also allows correctness assertions proved by symbolic indexing to be composed into larger properties, something previously not possible.